Experimental assessment of strengthening strategies against the out-of-plane collapse of masonry infills in existing RC structures - Maria Teresa De Risi (2019)
Past and more recent seismic events worldwide clearly showed that a crucial issue for lifesafety and loss reduction due to earthquakes for existing reinforced concrete (RC) buildings is related to the out-of-plane (OOP) collapse of infill masonry walls. In literature, few studies addressed this paramount topic, above all about the proposal of strengthening strategies to prevent the infills' collapse. This paper presents an experimental work about the assessment of possible strengthening solutions designed to mitigate or prevent the out-of-plane collapse of masonry infills in existing RC buildings. Three nominally identical full-scale one-bay-one-story RC frames were built and infilled with a thin masonry wall made up of horizontal hollow clay bricks. The first specimen was representative of the enclosure of a typical existing RC building in the Mediterranean region in its "as-built" condition. The remaining two specimens were strengthened against the out-of-plane collapse by means of two different strengthening techniques based on the application of innovative systems made up of high-ductility mortar plaster and fibre-reinforced polymer nets. All the tests consisted in the application of a semi-cyclic (loading-unloading-reloading) history of imposed displacements in the OOP direction by means of small pneumatic jacks through a uniform distributed load. Experimental results are shown in terms of OOP force-displacement responses, deformed shapes and damage evolution. In the end, the results of the tests are compared to assess the effectiveness of the selected strengthening techniques and to provide a support towards the choice of the best strategies for future further investigations and applications.